Chromium carbide coating of hot work tool steel X40CrMoV51 and nitriding steel 34CrAlNi7 by a thermoreactive diffusion process - Topuz, Ahmet; Karaaslan, Ahmet; Topuz, Polat (CARL HANSER VERLAG, 2007)
In this study tool steel and nitriding steel surfaces were coated with chromium carbide using a thermoreactive diffusion process. The chromium carbide coating process was carried out at 1000 degrees C for 5 hours, involving a powder of pure chromium, an inert filler (Al2O3), a carbon containing compound (C12H10) and an activator (NH4Cl). At the end of the thermally activated process, the carbide coatings were examined by means of optical microscopy, SEM, and micro hardness measurement. The measured thicknesses of the chromium carbide layers were 8 - 9 mu m for the hot work tool steel and 10 - 11 mu m for the nitriding steel. No cracks or delamination were found between the chromium carbide coating layers and the substrate material.
Keywords: Materials Science